Fracasso escolar e alfabetização: uma crítica ao período preparatório - Avani Avelar Xavier Lanza (1988)
The intention of this work is to raise a deeper reflection on the traditional fase os preparing for the teaching of reding already existing in schools. Starting from a theorical retaken of the question on evsion and repeating os students attending the first grade of an elementary school which has as a basis the teaching of reading and its multiple features, a study about the preparatory period for reading and writing learning is proposed, trying to detect the role it would play as to the relation between scholar failure and the teaching of reading. So a critics on pedagogical practicing developed a preparatory period of a public school is presented followed by a valuation of a group of children as to determined linguistic and psycholinguistic abilities concerning the teaching of reading. A critical study and the comparison among the development of thies group of children in three situations in the preparatory period, at the end of the school year, and in the selected abilities made it possible to achieve certain aspects which led us to a conclusion that there is a necesity of proceeding to a return into the practice of the preparatory period for the teaching of reading so that it fails to be a factor of discrimination, selection and predictio either of the suces of the failure of the student